Gonadal development and fecundity of the smooth weakfish Cynoscion leiarchus (Teleostei: Perciformes: Sciaenidae) in a tropical Brazilian bay - José P. do Carmo Silva; Marcus R. da Costa; Iracema D. Gomes; Francisco G. Araújo (Zoologia (Curitiba))
ABSTRACT Cynoscion leiarchus (Cuvier, 1830) is a coastal fish species that is widely distributed along the Western Atlantic coast, from Belize to Southern Brazil. In Brazil, C. leiarchus It is an important resource for commercial and artisanal fisheries. Our objective was to describe the oogenesis and spermatogenesis stages of the species and to estimate batch size and relative fecundity of a population at a tropical bay in southeastern Brazil. The examined specimens were obtained from artisanal catches that took place from July 2013 to June 2014. A total of 18 individuals (11 females and 7 males) were examined for histological analysis and 20 spawning-capable females were used to estimate fecundity. Five stages of oocyte development (primary growth, pre-vitellogenic, vitellogenic, oocyte maturation and atresia) and four stages of spermatocytes (spermatogonia, spermatocytes, spermatids, spermatozoa) were described in different phases of gonad development (immature, developing, spawning capable and regenerating), suggesting that spawning happens in batches, oocyte development is asynchronic and fecundity is indeterminate. Batch fecundity ranged from 100 × 103 to 866 × 103 oocytes undergoing final oocyte maturation, and relative fecundity ranged from 232 to 1,225 oocytes, averaging 467 oocytes per gram of ovary-free body weight. Fecundity tended to increase linearly with gonadal weight, total weight, total length, and age, but the highest linear correlation obtained was between fecundity and gonadal weight. This study provides the first information on the gonadal development of C. leiarchus from the Brazilian coast and is a baseline to compare with other populations and/or congeneric species.